Social deprivation and adult head injury: a national study. Issue 8 (21st July 2003) - Dunn, L; Henry, J; Beard, D
Abstract : Objectives: To establish the association between measures of social deprivation, mechanisms of injury, patterns of care, and outcome following closed head injury. Methods: All Scottish adult A&E attendees with closed head injury (AIS Head ≥3) between July 1996 and December 2000 were studied. Results: Trauma was more common in individuals from more deprived areas. Within the trauma population head injury was relatively more common in patients from deprived areas; these individuals were more likely to sustain an isolated head injury as a result of an assault. Admission GCS was higher and normal physiology (as assessed by the RTS) was more common in individuals from more deprived areas. Recorded co-morbidity was similar between the two groups with the exception of a history of alcohol or substance abuse which was more common among patients from more deprived areas. Similar proportions of patients from more deprived and less deprived areas were transferred to the Regional Neurosurgical Centre. For patients who were transferred directly from A&E, time to neurosurgical theatre was similar for both groups. Length of hospital and ITU stay was less in patients from more deprived areas. After adjusting for known predictors of outcome using logistic regression analysis, there was no significant difference in mortality between patients from more deprived and less deprived areas. Conclusions: Residing in a more deprived area is not associated with increased mortality from head injury among adults in Scotland. It is associated with different patterns of injury and a different process of care following presentation to hospital.